LIBRARIANS’ ROLE AS CHANGE AGENTS FOR INSTITUTIONAL REPOSITORIES: A CASE OF MALAYSIAN ACADEMIC LIBRARIES - Katayoon, Kamraninia; A., Abrizah (Malaysian Journal of Library and Information Science, 2010)
The primary reason for establishing an institutional repository is to increase the visibility of the institution’s research output by making it Open Access. Academic libraries are becoming very involved in managing electronic scholarly products and participating in the evolving scholarly communication process through institutional repositories. Although institutional repositories can make room for easier access to universities’ research output, unfortunately it is not fully developed in some academic institutions. The origin of this problem is that there are known instances where librarians in-charge of institutional nrepository are unaware of their roles, and are unskilled in implementing the institutional repository. This paper describes a study conducted on the roles of librarians in the deployment and content recruitment of institutional repositories in eight (8) universities in Malaysia. Sample for this study are librarians who are involved with the development and implementation of institutional repository in their respective universities. The study reveals that the act of collecting materials for depositing is mainly done by librarians rather than the authors and researchers. Providing training sessions, holding meetings in departments and faculties, and also linking of the institutional repository website from the university and faculties’ website have the highest rank in librarians’ approach to promote the institutional repository. The paper also discusses the process of depositing, motivation factors, roles, marketing and benefits of institutional repository that will have reference value for the librarians who desire to embark on an institutional repository